Pengaruh Isu PHK Terhadap Motivasi Karyawan yang Berdampak Terhadap Kinerja, Kepuasan Kerja, dan Retensi Karyawan - Felix Martinus; Sundring Pantja Djati (MES Management Journal, 2026)
The COVID-19 pandemic has resulted in layoffs, work disruptions, changes in work patterns, and psychological stress, posing challenges for companies in maintaining employee motivation, communication, and performance, particularly in the logistics industry, which has high operational demands. This study aims to analyze the relationship between layoffs, organizational communication, motivation, performance, and employee retention at PT Berkat Subuh Transpor. The study used a quantitative approach with a descriptive design. Data were obtained from 173 employees through purposive sampling and collected using an online questionnaire. Analysis was conducted using Structural Equation Modeling (SEM). The results show that layoffs have no significant effect on employee motivation or performance. Conversely, motivation has a positive and significant effect on employee performance and retention. Motivation also acts as a mediating variable between organizational communication and performance and job satisfaction. However, organizational communication has not been able to moderate or reduce the impact of layoffs on employee motivation. These findings emphasize the important role of motivation in improving employee performance, satisfaction, and retention in logistics companies.